Distinct Immunomodulatory and Migratory Mechanisms Underpin the Therapeutic Potential of Human Mesenchymal Stem Cells in Autoimmune Demyelination. Issue 8 (August 2013) - Payne, Natalie L.; Sun, Guizhi; McDonald, Courtney; Layton, Daniel; Moussa, Leon; Emerson-Webber, Ashley; Veron, Nadege; Siatskas, Christopher; Herszfeld, Daniella; Price, John; Bernard, Claude C. A.
Mesenchymal stem cells (MSCs) are efficacious in a variety of intractable diseases. While bone marrow (BM)-derived MSCs (BM-MSCs) have been widely investigated, MSCs from other tissue sources have also been shown to be effective in several autoimmune and inflammatory disorders. In the present study, we simultaneously assessed the therapeutic efficacy of human BM-MSCs, as well as MSCs isolated from adipose tissue (Ad-MSCs) and umbilical cord Wharton's jelly (UC-MSCs), in experimental autoimmune encephalomyelitis (EAE), an animal model for multiple sclerosis (MS). Prior to in vivo experiments, we characterized the phenotype and function of all three MSC types. We show that BM-MSCs were more efficient at suppressing the in vitro proliferation of mitogen or antigen-stimulated T-cell responses compared to Ad-MSCs and UC-MSCs. Notably BM-MSCs induced the differential expression of cytokines from normal and stimulated T-cells. Paradoxically, intravenous transplantation of BM-MSCs into C57Bl/6 mice with chronic progressive EAE had a negligible effect on the disease course, even when multiple MSC injections were administered over a number of time points. In contrast, Ad-MSCs had the most significant impact on clinical and pathological disease outcomes in chronic progressive and relapsing–remitting EAE models. In vivo tracking studies revealed that Ad-MSCs were able to migrate to the central nervous system (CNS), a property that most likely correlated with their broader expression of homing molecules, while BM-MSCs were not detected in this anatomic region. Collectively, this comparative investigation demonstrates that transplanted Ad-MSCs play a significant role in tissue repair processes by virtue of their ability to suppress inflammation coupled with their enhanced ability to home to the injured CNS. Given the access and relatively ease for harvesting adipose tissue, these data further implicate Ad-MSCs as a cell therapeutic that may be used to treat MS patients.